Two way bridges and one-way roads: comparing U.S. and Canadian approaches to minority communities and counterterrorism before and after 9/11 - Speed, Francesca (2018)
After the attacks of 9/11, it became imperative for domestic security and intelligence services in the United States and Canada to engage with Muslim communities to combat homegrown Islamist extremism. This represented a shift in the pre-9/11 approach, which had seen these services largely avoid engagement with visible minority communities in their respective jurisdictions. This thesis examines the differences in the pre- and post-9/11 approaches to terrorism emanating from minority communities in North America, and focuses particularly on the ways in which the United States and Canada have chosen to interact with Muslim communities after September 11. This thesis offers an analysis of these approaches, and how they differ from those to minority communities in an era of secular terrorism. It argues that the methods chosen by the two countries are divergent and require different characterisations, and that the Canadian approach has thus far been more effective in countering homegrown Islamist extremism.